Community knowledge of Australia’s national preventive health strategy focus areas: a nationally representative survey of 1509 adults - Amie Steel; Hope Foley; Jon Adams (BMC Public Health)
Abstract Background While some general patterns and trends of health information seeking and literacy in the Australian population are known, there is a need to understand these behaviours and skills specific to the focus areas outlined in the National Preventive Health Strategy (NPHS). Methods In response, this study employed a cross-sectional online survey of adults in the Australian general population (n = 1509) to investigate their knowledge and health information seeking behaviour regarding the NPHS’ seven focus areas. It also explored primary care practitioners as a preventive health information source. The survey consisted of 135 core items and 15 adaptive items including the Health Literacy Questionnaire (HLQ). The degree to which accessing information about a preventive health focus area from one of the three categories of health professional predicted the accuracy of the participant’s knowledge about that focus area was determined using logistic regression. Results A total of 1,535 complete responses were recorded, 26 of which were removed due to data integrity concerns, resulting in a final sample of n = 1,509. Participants were typically above mid-range for each of the HLQ scales. The sample was broadly representative of the Australian general population. Preventive health knowledge items about cancer screening and prevention were scored accurately by the most participants (85.2%), while the highest number of completely incorrect responses were immunisation (5.3%), alcohol intake (5%) and tobacco and nicotine addiction (4.9%). Participants who provided correct responses to both items about tobacco and nicotine addiction had decreased odds by of having accessed information about tobacco from a medical doctor (aOR 0.30), while those who answered items about immunisation correctly had lower odds of accessing information about immunisation from complementary medicine providers (aOR 0.30). Reporting completely correct responses to alcohol intake items was associated with lower odds of accessing information about alcohol from either medical doctors (aOR 0.46) or complementary medicine providers (aOR 0.17). Conclusions This research highlights the need for future research to investigate and understand some key issues challenging efforts to optimise effective preventive health initiatives with a view to informing better community health and wellbeing outcomes.